THE INVOLVEMENT OF ADVANCED COGNITIVE SKILLS IN VARIOUS FOOTBALL – SPECIFIC TESTS A PILOT STUDY - Bucz, Bence; Varga, Katalin; Pucsok, József Márton; Bíró, Melinda (Stadium - Hungarian Journal of Sport Sciences, 2024)
Sports professionals should encourage the development of cognitive functions as often as possible in training. Stimulating the brain with alternating stimuli can promote concentration, attention, and the development of situational awareness and decision-making skills. The more and more diverse stimuli the player receives, the faster and more effectively he will react to match situations. Our research examined the effect of exercises requiring advanced cognitive skills on the training load. Changes in cardiovascular data were monitored using Polar Verity Sense 4J and Polarflow systems. The pilot study involved a U-16 football player. Our results demonstrated that in addition to increasing speed, duration, and number of repetitions, the gradual inclusion of decision-making situations can also effectively increase the load. The participant completed two sets of exercises. During the second test, more complex exercises required advanced cognitive skills. The average heart rate for the first test was 130 beats per minute. We experienced an increase in the average value (150 beats per minute) during the completion of the second test. We measured an average 15 percent increase in the participants’ heart rate.